Simultaneous Multispacecraft Probing of Electron Phase Space Holes. Issue 21 (4th November 2018) - Tong, Y.; Vasko, I.; Mozer, F. S.; Bale, S. D.; Roth, I.; Artemyev, A.V.; Ergun, R.; Giles, B.; Lindqvist, P.‐A.; Russell, C.T.; Strangeway, R.; Torbert, R. B.
Abstract: We present a series of electron holes observed simultaneously on four Magnetospheric Multiscale spacecraft in the plasma sheet boundary layer. The multispacecraft probing shows that the electron holes propagated quasi‐parallel to the local magnetic field with velocities of a few thousand kilometers per second with parallel spatial scales of a few kilometers (a few Debye lengths). The simultaneous multispacecraft probing allows analyzing the 3‐D configuration of the electron holes. We estimate the electric field gradients and charge densities associated with the electrons holes. The electric fields are fit to simple 3‐D electron hole models to estimate their perpendicular scales and demonstrate that the electron holes were generally not axially symmetric with respect to the local magnetic field. We emphasize that most of the electron holes had a complicated structure not reproduced by the simple models widely used in single‐spacecraft studies. Plain Language Summary: We present the first measurement of electron holes (electrostatic solitary waves) by four Magnetospheric Multiscale spacecraft simultaneously. Such observation has allowed us to directly measure the charge density and to address the 3‐D structure of these electron holes both for the first time. The analysis of 3‐D configuration of the electron holes can be valuable for analysis of electron holes observed in space plasmas. Key Points: Simultaneous observations of electron phase space holes at four MMS spacecraft are presented The charge density within the electron holes is computed using the electric field measurements at four spacecraft The three‐dimensional configuration of the electron holes is analyzed, and the perpendicular scales are estimated